Propagation Methods for Berberis spp. Habituated in Nilgiri Hills - P NALLATHAMBI; C UMA MAHESWARI; JAGDISH KUMAR; N PREETHI; RAJESH KUMAR MEENA (Seed Research, 2026)
Berberis species are important concern in agriculture and especially on perpetuation and dissemination of Puccinia species. Pathogenesis studies involve uniform population of host as well as pathogen under favorable environmental conditions. Since large population of identical clones or species are essential required for our cross inoculations and pathogenesis studies between main (wheat) and probable alternate hosts (Barberry) systematic experiments were designed on propagation methods. Cumulative analysis of data revealed that the naked seeds expressed better germination (97.5%) seed germination than air layered plants. Seedlings uniformity and establishment were consistent in plants established from seeds compared to air layered plantlets. Seed germination percentage was ranging from 79.5 to 97.5 irrespective of the samples and locations in Nilgiri hills. However, we could select uniform seedlings at very young stage from seed germination experiments than air layered plantlets, wherein uniformity of flowering and seed maturity was not maintained. Present investigations conclude that pathogenesis of Puccinia species can be carried out in seedlings plants and rapid production of barberry fruits could be possible in air layered plants than seedling plants.